Mucormycosis experience through the eyes of the laboratory - ALTINKANAT GELMEZ, GÜLŞEN (TAYLOR & FRANCIS LTD, 2019)
Background: Mucormycosis is a rare, worldwide fungal infection with high mortality, which mostly affects immunocompromised patients. Compared to large parts of Asia, Europe, and the USA, information on clinical expression and fungal species distribution in mucormycosis in Turkey is limited. Objectives and methods: The main aim of this study was to evaluate the demographic features of mucormycosis cases, identify the isolates at the species level by using matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF), compare culture results with histopathological examination and determine the antifungal susceptibility patterns of the pathogens. Results: Between 2016 and 2018, 10 mucormycosis cases (six female, four male; age range: 35-74 years) were evaluated retrospectively. The predominance of the cases were in late autumn and winter. Diabetes mellitus was the most common underlying condition. Seven patients had rhinoorbitocerebral, two had pulmonary and one had cutaneous mucormycosis. By mycological culture and direct microscopic examination nine strains were identified as Rhizopus spp. and one as Mucor spp. Seven of these strains were identified at the species level by MALDI-TOF. Histopathological examination of eight tissues were reported as compatible with mucormycosis. All isolates were resistant to azoles and echinocandins. Two isolates were resistant to Amphotericin B and one was resistant to posaconazole. Surgical debridement combined with antifungal therapy was the main treatment option. The mortality rate was 40% (n = 4) and the mean number of days between the onset of complaints and the initiation of treatment was 9.25. Conclusions: Early, rapid and accurate diagnosis of mucormycosis is of critical importance in the treatment of immunosuppressed patients.
Keywords: Mucormycosis; MALDI-TOF; Rhizopus; antifungal susceptibility; histopathology; IDENTIFICATION; EPIDEMIOLOGY; RESISTANCE